Characterizations of endophytic Bacillus strains from tomato roots as growth promoter and biocontrol of Ralstonia solanacearum - YULMIRA YANTI; WARNITA WARNITA; REFLIN REFLIN; CHAINUR RAHMAN NASUTION (Biodiversitas Journal of Biological Diversity, 2018)
Yanti Y, Warnita, Reflin, Nasution CR. 2018. Characterizations of endophytic Bacillus strains from tomato roots as growth promoter and biocontrol of Ralstonia solanacearum. Biodiversitas 19: 906-911. Bacterial wilt caused by Ralstonia solanacearum is the most damaging vascular pathogens in tomato and many other crops in tropical, subtropical and warm temperate areas of the world limiting its production. Biological agents such as Plant growth Promoting Rhizobacteria (PGPR) is considered as a potential biological control agent for the suppression of plant diseases such as bacterial wilt. Bacillus spp. are one of the most potential genera of PGPR group used for controlling pathogens and promoting plant growth because of their spore-forming ability which increases their adaptation to the environment. The aims of the research were to isolate Endophytic Bacillus isolates, to characterize its ability as plant growth promoter and pathogen controller, and to identify its molecular genetic using 16S rRNA. Bacillus strains were isolated from healthy tomato roots. All Bacillus spp. strains acquired from isolation were then screened directly on plants in completely randomized design experiments with 3 replications. All potential strains were screened and identified using 16S rRNA with 27F and 1492R primers. Results showed that out of 15 obtained isolates, 6 of them showed a good ability to both promote growth and control R. solanacearum. All isolates were identified as B. Pseudomycoides strain NBRC 101232, B. cereus strain CCM 2010, B. toyonensis strain BCT-7112, B. anthracis strain ATCC 14578, B. cereus strain JCM 2152 and B. cereus ATCC 14579.